Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 2266 species occurrences available in GBIF matching the query: { "and" : [ "Country is Spain", { "or" : [ "TaxonKey is Plantago notata Lag.", "TaxonKey is Orobanche haenseleri Reut.", "TaxonKey is Apollonias barbujana subsp. ceballosi (Svent.) G.Kunkel", "TaxonKey is Ruta oreojasme Webb & Berthel.", "TaxonKey is Echium sventenii Bramwell", "TaxonKey is Crambe pritzelii Bolle", "TaxonKey is Parolinia intermedia Svent. & Bramwell", "TaxonKey is Minuartia webbii Mc Neill & Bramwell", "TaxonKey is Chenopodium coronopus Moq.", "TaxonKey is Helianthemum thymiphyllum Svent.", "TaxonKey is Convolvulus glandulosus (Webb) Hallier fil.", "TaxonKey is Convolvulus scoparius L. f.", "TaxonKey is Ocotea foetens (Aiton) Baill.", "TaxonKey is Gesnouinia arborea (L.fil.) Gaudich.", "TaxonKey is Nepeta hispanica Boiss. & Reut.", "TaxonKey is Ranunculus montserratii Grau", "TaxonKey is Androcymbium hierrense subsp. macrospermum U.Reifenb.", "TaxonKey is Rhus albida Greene", "TaxonKey is Sedum nevadense Coss.", "TaxonKey is Sedum aetnense Tineo", "TaxonKey is Spiraea crenata subsp. parvifolia (Pau) Romo", "TaxonKey is Cheirolophus arbutifolius (Svent.) G.Kunkel", "TaxonKey is Halimium calycinum (L.) K.Koch" ] } ] } The dataset includes 2266 records from 70 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0014804-160118175350007/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences